2023
DOI: 10.3390/ijms24076542
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Death-Associated Protein Kinase 1 Changes the Transcriptomic Profile and Alters Neural-Related Pathways in the Brain

Abstract: Death-associated protein kinase 1 (DAPK1), a Ca2+/calmodulin-dependent serine/threonine kinase, mediates various neuronal functions, including cell death. Abnormal upregulation of DAPK1 is observed in human patients with neurological diseases, such as Alzheimer’s disease (AD) and epilepsy. Ablation of DAPK1 expression and suppression of DAPK1 activity attenuates neuropathology and behavior impairments. However, whether DAPK1 regulates gene expression in the brain, and whether its gene profile is implicated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Functional studies demonstrated that DAPK1 KO mice have different presynaptic components in hippocampus compared with the WT mice, as evidenced by the increased paired-pulse ratio and reduced glutamate release probability in the hippocampus of KO mice [ 164 ]. Our transcriptomic analysis in DAPK1 KO and WT mice suggested that DAPK1 ablation globally changes the transcriptional profile in multiple brain regions and significantly regulates genes related to glutamatergic and GABAergic synaptic pathways [ 185 ]. The potential involvement of DAPK1 in modulating synaptic transmission and plasticity hints that DAPK1 dysregulation in AD may additionally cause synaptic impairments.…”
Section: The Role Of Dapk1 In Alzheimer’s Core Pathologiesmentioning
confidence: 99%
“…Functional studies demonstrated that DAPK1 KO mice have different presynaptic components in hippocampus compared with the WT mice, as evidenced by the increased paired-pulse ratio and reduced glutamate release probability in the hippocampus of KO mice [ 164 ]. Our transcriptomic analysis in DAPK1 KO and WT mice suggested that DAPK1 ablation globally changes the transcriptional profile in multiple brain regions and significantly regulates genes related to glutamatergic and GABAergic synaptic pathways [ 185 ]. The potential involvement of DAPK1 in modulating synaptic transmission and plasticity hints that DAPK1 dysregulation in AD may additionally cause synaptic impairments.…”
Section: The Role Of Dapk1 In Alzheimer’s Core Pathologiesmentioning
confidence: 99%